Motivational factors in learning chemistry among chinese national-type secondary school students in Negeri Sembilan /Jenne Lee Ling Huey - 398696 Lee, Jenne Ling Huey; Aziz Nordin, supervisor; Fakulti Pendidikan (2009)
Project Paper (Sarjana Muda Sains serta Pendidikan (Kimia)) - Universiti Teknologi Malaysia, 2009